Exploring the hotspots and frontiers of voluntary disclosure studies around the world using bibliometric analysis - Mohd Shazwan Mohd Ariffin; Wan-Nordin Wan-Hussin; Siti Seri Delima Abdul Malak (Penerbit Universiti Kebangsaan Malaysia, 2021)
Voluntary disclosure is additional information beyond mandatory disclosure. Nowadays, the information sources available for stakeholders to make informed decision are not limited to annual reports. The first publication on voluntary disclosure started in 1979. As of January 12, 2020, a total of 520 publications on voluntary disclosure in the subject areas business, management, accounting, economics and finance were retrieved from Scopus core collection and analyzed. The study used bibliometric analysis to summarize the state of knowledge and development trends of voluntary disclosure. The study enhanced our understanding of the firms’ information environment which is critical for the functioning of an efficient capital market in promoting corporate transparency.